ANALISIS TINGKAT PENGETAHUAN DAN FAKTOR YANG MEMPENGARUHI PEMBELIAN PRODUK MAKANAN DAN MINUMAN HALAL PADA SISWA SMP DI KOTA SEMARANG - Hastuti, Dewi; Farikha Maharani; Tri Siswanti; Ludiro Santoso; Masrochatun; Muchamad Priyo Utomo (Universitas Mathla’ul Anwar Banten, 2025)
The purpose of the study was to determine the effect of knowledge level, religiosity, health safety of halal food and beverage, and school origin on the decision of junior high school students to purchase halal food and beverage products in Semarang City. This type of research is quantitative research with correlational nature. The sampling technique used was non probability sampling with purposive sampling method. The number of samples used for this study were 108 respondents consisting of 54 general junior high school students and 54 religious junior high school students. The data collection technique used was interview with questionnaire. The data analysis technique used is the classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, hypothesis testing there is a multiple linear regression test, namely the f test and t test. Based on the results and discussion, it shows that the level of knowledge, religiosity, halal food health safety and school origin together (f test, p = 0.000 <0.01) have a positive and very significant influence on purchasing decisions. While partially (t test) school origin (p = 0.109> 0.05) has an insignificant effect, while other independent variables level of knowledge (p = 0.000 <0.05), religiosity (p = 0.020 <0.05) and health safety of halal food and beverages (p = 0.015 <0.05) have a significant effect on purchasing decisions. In conclusion, the purchasing decisions of halal food and beverages of junior high school students from religious-based schools and students from national public-based schools in Semarang City have similar perceptions, and what influences purchasing decisions is the level of knowledge, religiosity and healthy safety of halal food and beverages.